2004
DOI: 10.1103/physrevb.70.184407
|View full text |Cite
|
Sign up to set email alerts
|

Disorder-induced depression of the Curie temperature in mechanically milledGdAl2

Abstract: Shand, P.M.; Stark, C.; Pekarek, T.M.; Yue, Lanping; Petkov, V.; and Leslie-Pelecky, Diandra, "Disorder-induced depression of the Curie temperature in mechanically milled GdAl 2 " (2004 The effect of disorder on the ferromagnetic transition is investigated in mechanically milled GdAl 2 . GdAl 2 is a ferromagnet when crystalline and a spin glass when amorphous. Mechanical milling progressively disorders the alloy, allowing observation of the change from ferromagnetic to a disordered magnetic state. X-ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 35 publications
2
23
0
1
Order By: Relevance
“…Furthermore, the value for the relative shift per frequency decade ∆T f /T f ∆logν = 0.0026(3) is similar to those reported for glassy magnets [24]. Quantitatively, the frequency dependence of the maximum can be reproduced by a phenomenological Vogel-Fulcher law using ν 0 = 10 13 Hz, a value typical for spin-glass systems [24]. The result of the fitting yields a value of T 0 = 41 K for the interaction temperature and E a /k B = 64 K for the activation energy, as shown in the inset of figure 9 a.…”
Section: Milled Tbal 2 Samplessupporting
confidence: 78%
“…Furthermore, the value for the relative shift per frequency decade ∆T f /T f ∆logν = 0.0026(3) is similar to those reported for glassy magnets [24]. Quantitatively, the frequency dependence of the maximum can be reproduced by a phenomenological Vogel-Fulcher law using ν 0 = 10 13 Hz, a value typical for spin-glass systems [24]. The result of the fitting yields a value of T 0 = 41 K for the interaction temperature and E a /k B = 64 K for the activation energy, as shown in the inset of figure 9 a.…”
Section: Milled Tbal 2 Samplessupporting
confidence: 78%
“…17 This maximum is virtually absent in the 20 h milled alloy and practically disappears for 120 h of milling time samples ͑probably as a result of the disorder increase͒, which is induced by the milling process. [4][5][6][7][8][9] Regarding the high-temperature maximum ͑usually associated with the Kondo temperature in these IV systems͒, 18 there is a slight decrease ͑1%-2%͒ in the position directly affected by the mentioned Curie-Weiss behavior of the Yb 2 O 3 . However, the absolute value of the magnetic susceptibility decreases 14%, 25%, and 30% for 20, 70, and 120 h of milling time, respectively, which is a significant sign of an increasing presence of Yb 2+ contribution.…”
Section: B DC Magnetic Susceptibilitymentioning
confidence: 99%
“…In this case, the relationship between the structural and magnetic changes induced by the milling process results in the evolution from a ferromagnetic behavior to a spin-glass phase, which emerges at lower temperatures. [4][5][6][7][8] More recently, a study of the magnetic properties of TbAl 2 milled alloys has revealed that not only disorder but also size effects are important in crucial understanding of the magnetic behavior, with a pronounced variation of coercivity with the grain size. 9 The relevance of the extension of these studies of nanocrystalline particle systems to Ce and Yb intermetallics, the latter being known as strongly correlated electron materials, requires some understanding of how macroscopic properties in these systems become modified at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there are consistent investigations on MNPs of rare Earth (R)-based alloys (Zhou and Bakker 1995;Li et al 2013;Morales et al 2004;Wang et al 2007;de Paula et al 2016;Sánchez-Valdés et al 2014;Rojas et al 2007;EchevarriaBonet et al 2013;Echevarria-Bonet et al 2015). These studies are much less widespread than the usual investigations of Fe, Ni, Co oxide MNPs (Tartaj et al 2003;Estrader et al 2013;RinaldiMontes et al 2015), although some of these R-based alloys allow for technological transfer as permanent magnets or magnetocaloric materials (Wang et al 2007;de Paula et al 2016;Sánchez-Valdés et al 2014).…”
Section: Introductionmentioning
confidence: 99%